2019
DOI: 10.1002/prot.25689
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure‐based characterization of ubiquitination sites in human and yeast proteins using Chou's sample formulation

Abstract: Ubiquitination is an important post‐translational event responsible for half‐life and turnover of proteins inside the cell. Proteins are ubiquitinated by forming an iso‐peptide bond between their lysine residue and C‐terminal glycine residue of ubiquitin leading to rapid degradation of proteins by 26S proteosome complex. Deregulation of ubiquitination is manifested by aberrant expression of E3‐ligase activity or mutation in the surroundings of ubiquitination sites. Many new experimentally validated ubiquitinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
(121 reference statements)
2
2
0
Order By: Relevance
“…Proteome-wide mapping of yeast ubiquitination sites and analysis of the protein primary structure identified the amino acids over-represented (A, E, G, K, Q, and R) and under-represented (L, F, H, and W) around ubiquitinated sites in yeast . This is somewhat similar with our finding of A and Q and A and G being over-represented in the proximity of in vivo and in vitro N -Hcy-Lys sites, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Proteome-wide mapping of yeast ubiquitination sites and analysis of the protein primary structure identified the amino acids over-represented (A, E, G, K, Q, and R) and under-represented (L, F, H, and W) around ubiquitinated sites in yeast . This is somewhat similar with our finding of A and Q and A and G being over-represented in the proximity of in vivo and in vitro N -Hcy-Lys sites, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…51 Proteome-wide mapping of yeast ubiquitination sites and analysis of the protein primary structure identified the amino acids over-represented (A, E, G, K, Q, and R) and underrepresented (L, F, H, and W) around ubiquitinated sites in yeast. 52 This is somewhat similar with our finding of A and Q and A and G being over-represented in the proximity of in vivo and in vitro N-Hcy-Lys sites, respectively. Although there are also differences, our other over-represented residues are L, V, and P, while under-represented residues are K, R, S, N, and D. The secondary structure analysis of in vivo N-homocysteinylated sites revealed that there is a tendency of the beta strand to be a preferred structure, while in the case of ubiquitination sites, a tendency for sheet, turn, and coil conformation is observed.…”
Section: Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…It has one irregular secondary structure type, the coil region, along with two regular secondary structure states, the -helix (H), and -strand (E) (C). Structural information has been applied to several types of PTM prediction, including succinylation [ 36 ], ubiquitination [ 37 ], and malonylation [ 38 ]. However, as far as we are aware, it has not yet been used for Kglu's prediction.…”
Section: Methodsmentioning
confidence: 99%